2005
DOI: 10.1038/oby.2005.19
|View full text |Cite
|
Sign up to set email alerts
|

Low Recognition of Childhood Overweight and Disease Risk among Native‐American Caregivers**

Abstract: ADAMS, ALEXANDRA K., RACHEL A. QUINN, AND RONALD J. PRINCE. Low recognition of childhood overweight and disease risk among Native-American caregivers. Obes Res. 2005;13:146 -152. Objectives: Pediatric obesity is a significant and increasing problem in Native-American communities. The aim of this study was to determine whether parents and other caregivers from three Wisconsin tribes recognized overweight children. We also assessed caregiver attributes associated with levels of concern for risk of future overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
4
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 24 publications
8
84
4
11
Order By: Relevance
“…We found correlation between maternal verbal and visual evaluation of the child. Adams et al 24 compared perception rates of mothers and fathers and found that fathers less likely recognized overweight in their children 24 . However, maternal and paternal verbal assessments of child's weight status were correlated, and related to child's BMI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found correlation between maternal verbal and visual evaluation of the child. Adams et al 24 compared perception rates of mothers and fathers and found that fathers less likely recognized overweight in their children 24 . However, maternal and paternal verbal assessments of child's weight status were correlated, and related to child's BMI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was observed that food consumption in children was adjusted according to the stimuli induced by the food served by their caregivers or parents, instead of being regulated by the satiety and increased energy following the previously consumed meals (28) . In most cases, grandparents tend to believe that overweight signifies healthiness (29) or that young children may grow out of being overweight (30) . Another interpretation of this particular finding is probably based on the so-called 'post-World War II overfeeding syndrome' (31) referring to the post-war period in Greece when there was severely decreased accessibility to food.…”
Section: Discussionmentioning
confidence: 99%
“…65 In a study of Native Americans living on reservations, only 15% of the obese children were perceived as overweight, and the children who were perceived as overweight had a mean BMI at Ͼ99th percentile. 60 Even some parents who had brought their child to a weightassessment clinic said that they were not especially concerned about their child's weight. 66 Similarly, very few of the parents who brought their obese child to be screened for a weightmanagement program thought that their child was very overweight, although 62% did say that their child was a little heavy.…”
Section: Parental Perception Of Childrens Weight Statusmentioning
confidence: 99%
“…Only studies conducted in the United States are listed, although a number of similar studies have been conducted outside the United States. [54][55][56][57][58] Some of the studies focused specifically on minority children, [59][60][61][62][63][64] whereas others included multiethnic samples. [65][66][67][68][69][70] Many researchers selected participants from within a fairly narrow age range (eg, 2-5 years, 4 -8 years), whereas a few included a broader age range.…”
Section: Parental Perception Of Childrens Weight Statusmentioning
confidence: 99%